2011
DOI: 10.4317/medoral.17227
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implantitis: Associated microbiota and treatment

Abstract: Introduction: Peri-implantitis is a late complication of dental implant treatment, induced by microbiological changes. Since the disorder is frequent, a review is indicated of the microorganisms that influence it and of the existing treatment options. Objective: To conduct a literature review of the microbiota associated to peri-implantitis and the existing treatment options. Material and Method: A PubMed literature search was made of the studies on the microbiota associated to dental implants in healthy patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 31 publications
1
60
2
5
Order By: Relevance
“…Gram-positive aerobic bacteria such as Streptococcus mitis, Streptococcus sanguis and Streptococcus oralis were observed on dental implant surfaces surrounded by healthy oral environment [32]. However, it was also possible to find small concentrations of anaerobic Gram-negative bacilli on some implants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gram-positive aerobic bacteria such as Streptococcus mitis, Streptococcus sanguis and Streptococcus oralis were observed on dental implant surfaces surrounded by healthy oral environment [32]. However, it was also possible to find small concentrations of anaerobic Gram-negative bacilli on some implants.…”
Section: Introductionmentioning
confidence: 97%
“…These subgingival microbiota lead to an increase in pocket depth and alveolar bone loss, which may damage the soft and hard tissue around the implant [29]. The microbiota changes in the periimplantitis sites include an increased total bacterial quantity and the proportion of Aggregatibacter actinomycetemcomitans, Fusobacterium species, Prevotella intermedia and Porphyromonas gingivalis, a decrease in the percentage of cocci, and an important increase in the proportion of mobile organisms and spirochaetes [31][32][33].…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, A actinomycetemcomitans and P gingivalis, which can be found in healthy peri-implant biofilms in small numbers, have been suggested to be the predominant pathogens implicated in peri-implant destruction. 63 A major difference between implants and teeth (in a partially edentulous case) is that with implants, one is introducing a sterile object into an environment of widely variable existing microbiota, so the most important question to answer is whether the existing microbiota influences the progression to peri-implantitis. Quirynen and colleagues 64 showed that colonization of an implant occurs within 2 weeks of healing abutment placement, and that this flora was nearly identical to the adjacent teeth (same quadrant).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…When left untreated, peri-implantitis can result in loss of the dental implant [9,58]. Studies have reported a considerably high prevalence of peri-implantitis, with estimations ranging from 20% to 56% of the patients, depending on the time frame under investigation [59,60]…”
Section: Treatment Of P Gingivalis–related Infectionsmentioning
confidence: 99%